Local agency transition to balanced mix design. Issue 13 (10th November 2022) - Elias, Nicole G.; Hand, Adam J. T.; Sebaaly, Peter E.; Hajj, Elie Y.; Piratheepan, Murugaiyah; Gibson, Scott
ABSTRACT: Construction techniques and mix design methods are subjected to continuous development along with new inventions, technologies, and related implementation strategies. Due to recent materials introduced into asphalt mixtures such as modified asphalt binders, high percentages of Reclaimed Asphalt Pavement (RAP), warm mix technologies, recycling agents, and others, the asphalt industry is rapidly moving toward the Balanced Mix Design (BMD) method. Current asphalt mixture design methods are structured around meeting a range of volumetric requirements and sometimes other properties such as stability and/or moisture sensitivity. Although this allows for volumetric parameters to be monitored and controlled during production, it does not give much engineering insight as to how the mixture will perform under field conditions. The objective of this research was to assist the local agencies in Nevada with the transition from the Marshall method to the BMD, the latest methodology for designing asphalt mixtures, using the Superpave gyratory compactor and performance tests. Based on experimental data, the research team aimed to create an approach for an optimised, and high-performing mix designs with the use of 15% RAP along with an implementation plan that could be adopted by local agencies and serve as an example for other agencies.